Clones or clans: the genetic structure of a deep‐sea sponge, Aphrocallistes vastus, in unique sponge reefs of British Columbia, Canada. Issue 4 (1st February 2017) - Brown, Rachel R.; Davis, Corey S.; Leys, Sally P.
Abstract: Understanding patterns of reproduction, dispersal and recruitment in deep‐sea communities is increasingly important with the need to manage resource extraction and conserve species diversity. Glass sponges are usually found in deep water (>1000 m) worldwide but form kilometre‐long reefs on the continental shelf of British Columbia and Alaska that are under threat from trawling and resource exploration. Due to their deep‐water habitat, larvae have not yet been found and the level of genetic connectivity between reefs and nonreef communities is unknown. The genetic structure of Aphrocallistes vastus, the primary reef‐building species in the Strait of Georgia (SoG) British Columbia, was studied using single nucleotide polymorphisms (SNPs). Pairwise comparisons of multilocus genotypes were used to assess whether sexual reproduction is common. Structure was examined 1) between individuals in reefs, 2) between reefs and 3) between sites in and outside the SoG. Sixty‐seven SNPs were genotyped in 91 samples from areas in and around the SoG, including four sponge reefs and nearby nonreef sites. The results show that sponge reefs are formed through sexual reproduction. Within a reef and across the SoG basin, the genetic distance between individuals does not vary with geographic distance ( r  = −0.005 to 0.014), but populations within the SoG basin are genetically distinct from populations in Barkley Sound, on the west coast of Vancouver Island. Population structure was seen across all sample sites (global F ST  = 0.248), especially between SoG and non‐SoG locations (average pairwise F ST  = 0.251). Our results suggest that genetic mixing occurs across sponge reefs via larvae that disperse widely.